Institutional insecurity and the neoliberalization of the territory: mobility and public transport in Ensenada, Baja California, Mexico - Ríos Chávez, Ernesto; Zavala-Alvarez, Jose; Rosales Guerrero, Carlos Federico (Acta Universitaria, 2026)
This paper shows how mobility conditions in Ensenada, Baja California, respond, on the one hand, to uncertainties generated by the current institutional framework that severely limit government management of public transportation and, on the other hand, to economic criteria of neoliberalism imposing the use and configuration of urban space, which creates developed areas and marginalized zones. Ensenada is an example of how government investment in urban development is oriented to favor activities that privilege private income over public services, such as public transportation. Questionnaires were applied to users, following a chain sampling technique, and interviews were carried out with key informants. Additionally, a rigorous document review and analysis was done applying a discourse analysis method. In conclusion, an institutional and organizational redesign is proposed, searching for operational effectiveness in the public management of public transport and mobility in Ensenada.